Hypoxia-Associated Changes in Striatal Tonic Dopamine Release: Real-Time in vivo Measurements With a Novel Voltammetry Technique - Barath, Abhijeet S.; Rusheen, Aaron E.; Rojas Cabrera, Juan M.; Price, J. Blair; Owen, Robert L.; Shin, Hojin; Jang, Dong Pyo; Blaha, Charles D.; Lee, Kendall H.; Oh, Yoonbae (Frontiers in Neuroscience, 2020)
Introduction: Striatal tonic dopamine increases rapidly during global cerebral hypoxia. This phenomenon has previously been studied using microdialysis techniques which have relatively poor spatio-temporal resolution. In this study, we measured changes in tonic dopamine during hypoxia (death) in real time with high spatio-temporal resolution using novel multiple cyclic square wave voltammetry (MCSWV) and conventional fast scan cyclic voltammetry (FSCV) techniques. Methods: MCSWV and FSCV were used to measure dopamine release at baseline and during hypoxia induced by euthanasia, with and without prior alpha-methyl-p-tyrosine (AMPT) treatment, in urethane anesthetized male Sprague-Dawley rats. Results: Baseline tonic dopamine levels were found to be 274.1 ± 49.4 nM(n=5; mean ± SEM). Following intracardiac urethane injection, the tonic levels increased to a peak concentration of 1753.8 ± 95.7 nM within 3.6 ± 0.6 min(n=5), followed by a decline to 50.7 ± 21.5 nM(n=4) at 20 minutes. AMPT pre-treatment significantly reduced this dopamine peak to 677.9 ± 185.7 nM (n=3). FSCV showed a significantly higher (p = 0.0079) peak dopamine release of 6430.4 ± 1805.7 nM(n=5) during euthanasia-induced cerebral hypoxia. Conclusion: MCSWV is a novel tool to study rapid changes in tonic dopamine release in vivo during hypoxia. We found a 6-fold increase in peak dopamine levels during hypoxia which was attenuated with AMPT pre-treatment. These changes are much lower compared to those found with microdialysis. This could be due to improved estimation of baseline tonic dopamine with MCSWV. Higher dopamine response measured with FSCV could be due to an increased oxidation current from electroactive interferents.